Molecular machines in biology : workshop of the cell - Frank, J. (Joachim), 1940- (Cambridge : Cambridge University Press, 2011)
'This edited volume discusses the concept of molecular machines, their intricate architecture, and new techniques that are being used to better understand the processes in the cell driven by molecular machines'--Provided by publisher.
'The concept of molecular machines in biology has transformed the medical field in a profound way. Many essential processes that occur in the cell, including transcription, translation, protein folding, and protein degradation, are all carried out by molecular machines. This volume focuses on important molecular machines whose architecture is known and whose functional principles have been established by tools of biophysical imaging (X-ray crystallography and cryo-electron microscopy) and fluorescence probing (single-molecule FRET). This edited volume includes contributions from prominent scientists and researchers who understand and have explored the structure and functions of these machines. This book is essential for students and professionals in the medical field who want to learn more about molecular machines'--Provided by publisher.
1. Single-molecule FRET: technique and applications to the studies of molecular machines / Xinghua Shi and Taekjip Ha -- 2. Visualization of molecular machines by cryo-electron microscopy / Joachim Frank -- 3. Statistical mechanical treatment of molecular machines / Debashish Chowdhury -- 4. Exploring the functional landscape of biomolecular machines via elastic network normal mode analysis / Karunesh Arora and Charles L. Brooks III -- 5. Structure, function, and evolution of archaeo-eukaryotic RNA polymerases -- gatekeepers of the genome / Finn Werner and Dina Grohmann -- 6. Single-molecule fluorescence resonance energy transfer investigations of ribosome-catalyzed protein synthesis / Daniel D. MacDougall, Jingyi Fei and Ruben L. Gonzalez, Jr. -- 7. Structure and dynamics of the ribosome as revealed by cryo-electron microscopy / Xabier Agirrezabala and Mikel Valle -- 8. Viewing the mechanisms of translation through the computational microscope / James Gumbart, Eduard Schreiner, Leonardo G. Trabuco, Kwok-Yan Chan and Klaus Schulten -- 9. The ribosome as a Brownian ratchet machine / Alexander S. Spirin and Alexei V. Finkelstein -- 10. T he GroEL/GroES chaperonin machine / Arthur L. Horwich and Helen R. Saibil -- 11. ATP synthase -- a paradigmatic molecular machine / Thomas Meier, Jose; Faraldo-Gez and Michael Bsch -- 12. ATP-dependent proteases: the cell's degradation machines / Sucharita Bhattacharyya, Shameika R. Wilmington and Andreas Matouschek.
Includes bibliographical references and index.
Keywords: Microbiology; Molecular biology; Biochemistry; Cell physiology; Electron microscopy; Molecular Biology; Cell Physiological Phenomena; Computational Biology; Microbiology; Models, Biological